AN ALGORITHMIC 3D ROCK ROUGHNESS MEASURE USING LOCAL DEPTH MEASUREMENT CLUSTERS - Herda H.H.W. (My University, 2006)
A computational algorithm which uses depth data from a reference plane to a rock fracture surface in calculating a new three-dimensional joint roughness coefficient is presented. Two independent sets of fracture data are investigated. The new coefficient is compared to Barton’s 2D joint roughness coefficient JRC. A measure indicating corrupt data is discussed. The algorithm is also used to show that, in general, rock roughness is only a local variable, not a directional one.
Keywords: ROCK ROUGHNESS; ALGORITHM; JOINT ROUGHNESS COEFFICIENT